Simplifying transfemoral ACURATE neo implantation using the TrueFlow nonocclusive balloon catheter. Issue 6 (23rd January 2020) - Toggweiler, Stefan; Loretz, Lucca; Brinkert, Miriam; Bossard, Matthias; Wolfrum, Mathias; Moccetti, Federico; Berte, Benjamin; Cuculi, Florim; Kobza, Richard
Abstract: Objectives: This study aimed to investigate the safety and efficacy of ACURATE neo transcatheter aortic valve replacement (TAVR) facilitated by predilatation with the nonocclusive TrueFlow balloon catheter. Background: Now that TAVR is moving forward, physicians have attempted to simplify and streamline the procedure and the so‐called minimalist approach has become more popular. Methods: We enrolled 142 patients (mean age: 82 ± 5 years, 61% female) in a prospective registry. Patients at low risk for intraprocedural third‐degree atrioventricular block (AVB) underwent TAVR with the TrueFlow balloon without rapid pacing and without insertion of a provisional pacemaker ( n = 121). The remaining 21 patients were predilated with rapid pacing using a provisional pacemaker and a standard balloon. Results: Predilatation with the TrueFlow balloon was successful in all 121 patients. Postdilatation was less frequently required after predilatation with the TrueFlow (25% vs. 57%, p = .003). Moreover, median procedural duration with the TrueFlow was significantly shorter (42 [interquartile range, IQR: 34–53] vs. 55 [IQR: 46–61] min, p = .004). In‐hospital outcomes were similar. At 30 days, there was no mortality, two (1%) patients had suffered a stroke and only four (3%) had required implantation of a new pacemaker. Conclusion: Among patients with a low risk for intraprocedural third‐degree AVB, the TrueFlow nonocclusive balloon catheter facilitates implantation of the ACURATE neo without the necessity of rapid pacing and a provisional pacemaker.